Leptophytum flavescens comb. nov. (Corallinales, Rhodophyta), an Arctic endemic from the sublittoral of NW Spitsbergen, North Norway, and western Novaya Zemlya, with epitypification of L. laeve. Issue 5 (27th May 2016) - Athanasiadis, Athanasios
ABSTRACT: Type material of Lithothamnion flavescens Kjellman, originally described from Karlsøy (Troms) and Karmakul Bay (Novaya Zemlya), is re-examined and a lectotype is selected. Type specimens and other collections from NW Spitsbergen and North Norway possess distinctive characters of the genus Leptophytum, including the development of flattened epithallial cells, short subepithallial cells, and simple spermatangial structures. Leptophytum flavescens (Kjellman) comb. nov. resembles the generitype Leptophytum laeve, differing in having: (1) a thicker perithallium, to 900 µm (vs. 350 µm in L. laeve ), that embeds older conceptacles, and (2) non-differentiated (in size or shape) pore cells of multiporate roofs. An epitype for L. laeve is also selected, which consolidates the status of this species and the genus, in agreement with the current literature and all publications prior to 1996.